Molecular Study of COL1A1 Gene in Women with Osteoporosis in Mosul City - Maryam M. Alani; Haitham L. Al-Hayali (African Journal of Advanced Pure and Applied Sciences, 2023)
Among the most prevalent diseases in the world is osteoporosis, and it is identified by the changes that occur in bone mineral density according to international health standards, and the disease is diagnosed by dual-energy X-ray DEXA. Osteoporosis is divided into two types (primary and secondary), where the primary type is in elderly men and women due to aging and in women in menopause. As for secondary osteoporosis, it is the result of different diseases and treatments, or because of tumors, cancerous diseases, systemic diseases, and endocrine diseases. Different diets, wrong diets, and lack of exercise are all causes of osteoporosis. Between September and November of the year 2021, private pathological analysis laboratories in Mosul reviewed (96) women with ages ranging from (45 to 35) years. Based on the disease's clinical cases, samples were chosen. The samples were separated into two groups in accordance with the outcomes of the biochemical analysis: The first category: 25 women who had no problems made up this group, which acted as a control group. The second group: Biochemical results revealed that 71 women in this group had osteoporosis. The results for women with osteoporosis for the COLA1 gene showed that the frequency value of the mutated genotype AA in the group of women with osteoporosis was 10%, which is the lowest compared to the mutated genotype in the control group of 5%, while the value of the healthy (normal) AA genotype was the same. The highest rate was Compared to the healthy group, where the percentage of individuals with a healthy (normal) genotype was more than 90%, there were 62% more women with osteoporosis. Regarding the heterogeneous genotype AC, there were 28% more observations in the group of infected women than there were in the 5% control group. In terms of allelic recurrence, the findings revealed that the patients' group had a higher incidence of the mutant allele A 23% compared to 8% in the control group. Natural allele prevalence in patients was 62%, as opposed to 92% in the control group. It turns out that we have a wide variety of genetic variants, which can be further broken down into two main categories: transition variations and (Transversion) variations. The locations of these variations depend on the type of heterogeneous bases. The study's findings also revealed a genetic link between variances and several genotypes and biochemical indicators of osteoporosis.